Social returns to commuting in the Baltic states - Mihails Hazans (European Regional Science Association (ERSA), 2002)
To what extent does commuting reduce regional wage disparities? This question is addressed by estimating two sets of earnings functions (based on 2000 LFS data for Estonia, Latvia and Lithuania): with geographical variables (like capital city, rural etc.) measured at the working place and at the place of residence. The main finding is that commuting has narrowed the ceteris paribus wage gap between capital city and rural areas by impressive 16 percentage points in Estonia and by 11 percentage points in Latvia, while the gap between capital and other cities has been reduced by 9 percentage points in both countries. In Lithuania gains from commuting are modest (3 percentage points) and go exclusively to residents of small cities. In the case of Latvia data allowed to estimate also effect of the distance between capital city and working place on wages, as well as individual returns to commuting in terms of the distance between living place and working place.
Keywords: 330